PRODUKTIVITAS DAN BIAYA ANGKUTAN TRUK DI TIGA KPH PERUMPERHUTANI, JAWA TENGAH - Dulsalam Apul Sianturi (Jurnal Penelitian Hasil Hutan, 1988)
An  investigation  on  truck   hauling of  logs  has been carried out  at three Perhutani  Forest  Districts in Central Java, in 1980, 1981 and 1982. The investigation comes to the following  conclusions: Annual   working  days  for gasoline trucks  range from  689 to l,676   hours with  an average  of 1,240 hours, and that for diesel trucks from  671 to 811 hours with an average of  790 hours.Effective  hauling output of gasoline iruchs in ton-km/year  ranges from 9,833 to 65,482  with an average of 33,000, and that  for  diesel  trucks  from  6,683 to  108,948 with  an average of  33,650.Hauling cost by  gasoline  truck in Rp per ton-km for  the years  1980, 1981, 1982  increases from year  to year,  namely Rp  95, Rp  128 and Rp  169, and that by diesel truck  Rp 78, Rp  80 and Rp 83, consecutively.                                          Hauling cost  by gasoline  truck  is higher than  that  by diesel truck.The highest component cost of hauling logging by gasoline truck  is fuel, i.e. 43 percent, and that at diesel  truck, spare parts, i.e. 62 percent